Functional morphology of the ankle extensor muscle‐tendon units in the springhare Pedetes capensis shows convergent evolution with macropods for bipedal hopping locomotion. Issue 3 (25th June 2020) - Veiga, Gabriela N.; Biewener, Andrew A.; Fuller, Andrea; van de Ven, Tanja M. F. N.; McGowan, Craig P.; Panaino, Wendy; Snelling, Edward P.
Abstract: This study assesses the functional morphology of the ankle extensor muscle‐tendon units of the springhare Pedetes capensis, an African bipedal hopping rodent, to test for convergent evolution with the Australian bipedal hopping macropods. We dissect and measure the gastrocnemius, soleus, plantaris, and flexor digitorum longus in 10 adult springhares and compare them against similar‐sized macropods using phylogenetically informed scaling analyses. We show that springhares align reasonably well with macropod predictions, being statistically indistinguishable with respect to the ankle extensor mean weighted muscle moment arm (1.63 vs. 1.65 cm, respectively), total muscle mass (41.1 vs. 29.2 g), total muscle physiological cross‐sectional area (22.9 vs. 19.3 cm 2 ), mean peak tendon stress (26.2 vs. 35.2 MPa), mean tendon safety factor (4.7 vs. 3.6), and total tendon strain energy return capacity (1.81 vs. 1.82 J). However, total tendon cross‐sectional area is significantly larger in springhares than predicted for a similar‐sized macropod (0.26 vs. 0.17 cm 2, respectively), primarily due to a greater plantaris tendon thickness (0.084 vs. 0.048 cm 2 ), and secondarily because the soleus muscle‐tendon unit is present in springhares but is vestigial in macropods. The overall similarities between springhares and macropods indicate that evolution has favored comparable lower hindlimb body plans for bipedal hopping locomotion in the two groups of mammals that last shared a common ancestor ~160 million years ago. The springhare's relatively thick plantaris tendon may facilitate rapid transfer of force from muscle to skeleton, enabling fast and accelerative hopping, which could help to outpace and outmaneuver predators. Abstract : The springhare's overbuilt plantaris tendon likely allows rapid transfer of force from muscle to skeletal attachment points, facilitating fast and accelerative hopping in predator‐dense habitats.